PELATIHAN PRODUKSI BAHAN BANGUNAN UNTUK MENINGKATKAN KETERAMPILAN MASYARAKAT DI PROVINSI BANTEN - Fitri Aida Sari; Telly Rosdiyani (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2021)
Banten Province has large natural resources, especially natural resources in the form of wood. The amount of natural resources must be accompanied by human resources who can process natural resources so that they have a high selling value. KOTAKU, which operates under the Direktorat Jenderal Cipta Karya Kementerian Pekerjaan Umum dan Perumahan Rakyat in collaboration with the University of Banten Jaya, conducts training for the community to produce building materials, especially in the production of frames and doors. The objectives of the implementation of these activities include increasing the capacity of the community in producing building materials, especially the manufacture of frames and doors and as an effort to improve the economy of the people in Banten Province. This activity is carried out for four days by presenting instructors who have qualifications and experience in producing building materials. The target of this activity is the people living in the Banten Province, especially Lebak Regency, Serang City, and Serang Regency. After participating in this training activity, the community is expected to have better skills and abilities in processing wood and can create jobs, both for themselves and for others.